Partisipasi Petani Pada Pasar Lahan (Studi Kasus Pada Petani Kentang Jawa Barat) - Elly Rasmikayati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. The objective of this study is to describe the participation of farmers on the land market. The research method used was a survey method and the PRA method (Participatory Rural Appraisal) were performed on 500 potato farmers in West Java were selected using two-stage stratified sampling technique. Descriptive statistics are used to describe the participation of farmers on the land market. Research results revealed that potato farmers participating in the land market through land leasing (51%), purchase of land (4%), land sales (9%) and farmers who do not actively participate in the land market as much as 36%. Meanwhile, there are exciting things, an increase in tenure of land area to farmers with land area less than 0.5 hectares.